Social media engagement and domestic violence awareness: women victims' experiences - Drina Intyaswati; Siti Maryam; Windhi Tia Saputra; Mohamad-Noor Salehhuddin Sharipudin (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Women must grasp the idea of domestic abuse in order to anticipate if they spot incidents of it.  The purpose of the study was to evaluate the relationship between perceptions of domestic violence and online community engagement on social media. This study used a survey method by distributing questionnaires through social media. The population were women social media users and used purposive sampling techniques with the criteria that respondents were married or had been married, had been victims of domestic violence (physical or mental), and had accessed domestic violence issues on social media in the last six months. Data collection was carried out in July-August 2024. The data was obtained from 300 women and analyzed using the SPSS 25 application. The results show that there is a significant correlation between perceptions of domestic violence and online community engagement in the community of domestic violence victims on social media. However, the strength of the relationship is low. Further analysis shows that the differences in respondents' community engagement levels were divided into three perception ownership groups. The findings suggest that women victims of domestic violence might join groups on social media to receive direction and counsel meant to assist with their issues.